Oxidation reactions of cellular and acellular hemoglobins: Implications for human health - Alayash, Abdu I. (Frontiers in Medical Technology, 2022)
Oxygen reversibly binds to the redox active iron, a transition metal in human Hemoglobin (Hb), which subsequently undergoes oxidation in air. This process is akin to iron rusting in non-biological systems. This results in the formation of non-oxygen carrying methemoglobin (ferric) (Fe3+) and reactive oxygen species (ROS). In circulating red blood cells (RBCs), Hb remains largely in the ferrous functional form (HbF2+) throughout the RBC's lifespan due to the presence of effective enzymatic and non-enzymatic proteins that keep the levels of metHb to a minimum (1%–3%). In biological systems Hb is viewed as a Fenton reagent where oxidative toxicity is attributed to the formation of a highly reactive hydroxyl radical (OH•) generated by the reaction between Hb's iron (Fe2+) and hydrogen peroxide (H2O2). However, recent research on both cellular and acellular Hbs revealed that the protein engages in enzymatic-like activity when challenged with H2O2, resulting in the formation of a highly reactive ferryl heme (Fe4+) that can target other biological molecules before it self-destructs. Accumulating evidence from several in vitro and in vivo studies are summarized in this review to show that Hb's pseudoperoxidase activity is physiologically more dominant than the Fenton reaction and it plays a pivotal role in the pathophysiology of several blood disorders, storage lesions associated with old blood, and in the toxicity associated with the infusion of Hb-derived oxygen therapeutics.